2015
DOI: 10.1073/pnas.1522288113
|View full text |Cite
|
Sign up to set email alerts
|

Critical role of RAGE and HMGB1 in inflammatory heart disease

Abstract: Autoimmune response to cardiac troponin I (TnI) induces inflammation and fibrosis in the myocardium. High-mobility group box 1 (HMGB1) is a multifunctional protein that exerts proinflammatory activity by mainly binding to receptor for advanced glycation end products (RAGE). The involvement of the HMGB1-RAGE axis in the pathogenesis of inflammatory cardiomyopathy is yet not fully understood. Using the well-established model of TnI-induced experimental autoimmune myocarditis (EAM), we demonstrated that both loca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
111
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(119 citation statements)
references
References 61 publications
4
111
0
Order By: Relevance
“…These studies suggest that a critical component of disease pathogenesis in EAM is the release of DAMPs that drive inflammatory responses resulting in impaired LV function. 155 Monocytes may play an important role in EAM progression as inhibition of monocyte recruitment via CCR2 siRNA resulted in decreased immune cell infiltration, fibrosis, and increased cardiac function. This was observed when siRNA was injected either at the onset of disease or 21 days post-EAM induction, suggesting that monocytes play a role even at later stages after disease establishment.…”
Section: Experimental Autoimmune Myocarditismentioning
confidence: 99%
“…These studies suggest that a critical component of disease pathogenesis in EAM is the release of DAMPs that drive inflammatory responses resulting in impaired LV function. 155 Monocytes may play an important role in EAM progression as inhibition of monocyte recruitment via CCR2 siRNA resulted in decreased immune cell infiltration, fibrosis, and increased cardiac function. This was observed when siRNA was injected either at the onset of disease or 21 days post-EAM induction, suggesting that monocytes play a role even at later stages after disease establishment.…”
Section: Experimental Autoimmune Myocarditismentioning
confidence: 99%
“…Banger et al found that HMGB1 or RAGE knockout mice showed decreased physiological signs of cardiac impairment after suffering from an autoimmune response to cardiac troponin I [34], suggesting a role for this signaling pathway in inflammatory and immune responses. Our research found that expression of both RAGE and the nuclear NF-κB p65 subunit in the rat cortex increased significantly at 12h and 24h after CLP.…”
Section: Discussionmentioning
confidence: 99%
“…The importance of RAGE in myocardial inflammation was demonstrated in a study where RAGEdeficient mice were shown to have a reduced myocardial damage compared with wild-type mice [45] . Moreover, ablation of RAGE leads to a reduction in several inflammatory mediators that is important for the pathogenesis of autoimmune myocarditis [26] . In addition to binding to RAGE and TLRs, HMGB1 can also bind to other cytokines such as interleukin-1β.…”
Section: Discussionmentioning
confidence: 99%
“…HMGB1 can also promote growth of atherosclerotic plaques by triggering smooth muscle cell migration and proliferation [23,24] and stimulates activation of endothelial cells by enhancing the expression of adhesive molecules and cytokines [25] . Moreover, a recent publication shows that patients with myocarditis display increased local and systemic HMGB1 expression, and blocking HMGB1 signaling in vitro can reduce cardiac inflammation in animal models [26] . Thus, HMGB1 seems to play important roles in the pathophysiology of cardiovascular diseases.…”
Section: Introductionmentioning
confidence: 99%